2008
DOI: 10.1007/s10815-008-9271-9
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effect of desialylated erythropoietin administration on the frozen-thawed canine ovarian xenotransplantation

Abstract: Purpose The main drawback of ovarian cryopreservation followed by transplantation is that a large proportion of follicles are lost after transplantation. Thus, effects of erythropoietin (EPO) and desialylated EPO administration on the frozen-thawed canine ovarian xenotransplantation were examined. Methods The protective and survival-promoting effects of EPO and desialylated EPO on the follicles of frozen-thawed canine ovaries after transplantation were examined using NOD-SCID mice. Frozen-thawed dog ovarian ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
53
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 34 publications
1
53
0
Order By: Relevance
“…Thereafter, once the newly trained dogs are recognized as superior guide dogs, they can never reproduce [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, once the newly trained dogs are recognized as superior guide dogs, they can never reproduce [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the cryopreservation of ovarian tissues is a potentially significant technology for the preservation of the genetic resources of working dogs as well as other laboratory and domestic animals [3,4]. Several reports have indicated that follicular loss in the mammalian ovary is not drastically extended by the cryopreservation procedure itself [3][4][5]. It is believed that the reason the primordial follicle is observably resistant to cryoinjury is because the oocyte it contains has a relatively inactive metabolism and lacks a meiotic spindle, zona pellucida and cortical granules [6].…”
mentioning
confidence: 99%
“…In fact, a high percentage of oocytes as well as granulosa cells survive the cryopreservation and thawing procedures [3,[7][8][9]. Despite being able to survive freezing, it is well established that a large proportion of follicles are lost during the initial ischemia that occurs after transplantation of ovaries of mouse [10,11], sheep [12,13], dog [4,5] and human [14,15]. Most follicles that survive cryopreservation undergo ischemic loss during neovascularisation [16].…”
mentioning
confidence: 99%
See 2 more Smart Citations